Students’ Perceptions on Participating in Remote Learning Activities in the Time of Covid-19 Pandemic - Fareed Mohamed Nawastheen; S. A. S. Kaushalya Perera (Studies in Learning and Teaching, 2021)
The present study aimed to assess Sri Lankan school students’ perceptions on the experience of participating in remote learning activities (RLA) available to them during the time of COVID-19 pandemic. This study was conducted as a survey. Using the exponential non-discriminative snowball sampling technique, data were collected from 613 school students through a questionnaire administered as a Google Form. Data were analyzed as mean values, standard deviations, and percentages. Analysis of data revealed that majority of respondents (92%) were well aware of the various RLA. Majority of the respondents (62.6%) used mobile internet and 69.5% used prepaid services. The main challenges they faced were related to affordability, heavy load of educational content presented through RLA, and concerns on cyber security when engaging with RLA. To make opportunities for learning more accessible to learners, it is recommended that mobile data be made available to school students at low costs and all educational programs should be made available to them free of charge. In addition, devices such as tablets should be provided to all students in order to ensure equality of access to education. Further, studies on parents’ and teachers’ experiences with their children’s and students’ learning through RLA would complement the findings of this study.